La eficiencia y confiabilidad del sistema notarial y registral en los actos jurídicos aplicando la modernización tecnológica - Barreiro Moreira, Grety Jacqueline (2025)
This scientific article examines the efficiency and reliability of the notarial and registry system in legal acts through technological modernization. Aiming to deepen the transformation of the Ecuadorian notarial and registry system in response to the challenges of the digital era, highlighting the need to strengthen legal security through technological modernization. The general objective is to integrate technological principles that address the demands of the new digital age, improving efficiency, reliability, and legal security. The methodology applied in this scientific article is based on a qualitative and dogmatic-legal approach, relying on the analysis of laws, jurisprudence, and international experiences to identify progress made and pending challenges. The results include digitizing documents, implementing electronic signatures, and using online platforms to facilitate the execution of legal acts with greater speed and transparency. In conclusion, the technological modernization of the notarial and registry system is currently an inevitable and necessary reality to ensure efficiency, reliability, and operational continuity in the management of legal acts. This allows the consolidation of a more efficient, reliable system aligned with the needs of a digitized society in Ecuador.